Cultural studies - nye kulturstudiar som studiedisiplin - Høystad, Ole Martin (Tidsskrift for kulturforskning, 2010)
The first part of the article is a presentation of the tradition of cultural studies, especially as an educational discipline, its academic legitimacy and legacy in a Scandinavian context. Main focus is on British cultural studies and the so-called Birmingham school of contemporary cultural studies (CCCS), founded in 1964, and what characterizes this tradition theoretically and thematically. The theoretical foundation, development of and turns in cultural studies are represented by the founding fathers of the discipline, especially Raymond Williams and Stuart Hall and their lasting influence on the theory and practice of cultural studies. The second part of the article discusses some of the analytical tools most often applied in cultural studies, especially the interdisciplinary approach, which often has the character of a combined diachronic and synchronic analysis. Also the classical analytical model of ’the circuit of culture’ is presented and modified into a new analytical model of ’the multicultural circuit’ to be applied in the analysis of a contemporary multicultural society. To defend cultural studies against the accusation of constructivistic and linguistic reduction of reality, the concept of indexicality is introduced, also as a way to study contemporary culture.